ONE-POT BIOSYNTHESIS AND STRUCTURAL ELUCIDATION OF IRON-BIOCHAR NANOCOMPOSITES FROM WASTE COCONUT SHELLS (FUDMA JOURNAL OF SCIENCES, 2025)
This study explores the eco-friendly one-pot biosynthesis and structural characterization of iron-biochar nanocomposites (IBN) derived from waste coconut shells using Allamanda cathartica extract as a reducing agent. The synthesis process leveraged the phytochemical abundance of the plant extract and the porous structure of coconut biochar, resulting in a material with enhanced properties for environmental applications. Characterization techniques such as BET, XRD, SEM, HRTEM, EDX, and FTIR confirmed the successful integration of nanoscale iron into the biochar matrix. The BET analysis revealed a surface area of 34.035 m²/g, a pore size of 102.2356 Å, and a pore volume of 0.110914 cm³/g, indicating high adsorption potential. XRD patterns confirmed crystalline iron oxide phases, while SEM and TEM images revealed highly porous structures with uniformly dispersed iron nanoparticles. The FTIR identified OH, C-O and aromatic C=C stretching, and EDX confirmed the elemental composition, including iron, oxygen, silicon, aluminum, and carbon, ensuring structural stability and pollutant binding efficiency. Additionally, the phytochemical analysis of Allamanda cathartica extract identified alkaloids, flavonoids, and steroids, supporting its role as a green reducing agent. The study highlights the structural and functional advantages of IBN over unmodified biochar, emphasizing its increased surface area, porosity, and pollutant removal efficiency. Furthermore, the scalability and sustainability of the synthesis process underscore its potential for large-scale environmental applications, aligning with circular economy principles.
Keywords: Iron-biochar nanocomposite; Allamanda cathartica; Coconut-derived biochar; One-pot biosynthesis